The Allo‐ and Viral‐Specific Immunosuppressive Effect of Belatacept, but Not Tacrolimus, Attenuates With Progressive T Cell Maturation. Issue 2 (February 2014) - Xu, H.; Perez, S. D.; Cheeseman, J.; Mehta, A. K.; Kirk, A. D.
Abstract Tacrolimus impairs allo‐ and viral‐specific T cell responses. Belatacept, a costimulation‐based alternative to tacrolimus, has emerged with a paradoxical picture of less complete control of alloimmunity with concomitant impaired viral immunity limited to viral‐naïve patients. To reconcile these signatures, bulk population and purified memory and naïve lymphocytes from cytomegalovirus (CMV)‐seropositive (n = 10) and CMV‐seronegative (n = 10) volunteers were studied using flow cytometry, interrogating proliferation (carboxyfluorescein succinimidyl ester dilution) and function (intracellular cytokine staining) in response to alloantigens or CMV‐pp‐65 peptides. As anticipated, T cells from CMV‐experienced, but not naïve, individuals responded to pp‐65 with a small percentage of their repertoire (<2.5%) consisting predominantly of mature, polyfunctional (expressing interferon gamma, tumor necrosis factor alpha and IL‐2) T effector memory cells. Both CMV naïve and experienced individuals responded similarly to alloantigen with a substantially larger percentage of the repertoire (up to 48.2%) containing proportionately fewer polyfunctional cells. Tacrolimus completely inhibited responses of CMV‐ and allo‐specific T cells regardless of their maturation. However, belatacept's effects were decreasingly evident in increasingly matured cells, with minimal effect on viral‐specific triple cytokine producers and CD28‐negative allo‐specific cells. These data indicate that belatacept's immunosuppressive effect, unlike tacrolimus's, wanes on progressively developed effector responses, and may explain the observed clinical effects of belatacept.